Science Laboratory Learning Environment and Students’ Practices on Laboratory Safety - Mendez, Mercy Joy (SEAMEO QITEP in Science, 2023)
This paper aims to identify the significant relationship between the science laboratory learning environment and students’ practices on laboratory safety for education students who took at least one subject or course with laboratory unit in face-to-face classes. The data from this study came from 201 education students, collected through an online survey using Google Forms. The non-experimental descriptive correlational design, census approach was used to select the study participants, and standardised questionnaires were also utilised. The weighted mean, standard deviation, Pearson product-moment correlation design, and linear regression analysis were employed as statistical techniques. The study found that the science laboratory learning environment is at a very high level. Meanwhile, the students’ practices on laboratory safety, especially emergency response plans, work procedures, and chemical waste management, are at a very high level, while safety equipment and handling of experiments are observed at a high level. The results also showed a significant relationship between the science laboratory learning environment and students’ practices on laboratory safety. The domain of science laboratory learning environment that significantly predicts students’ practices is the material environment. The result implied that the institution may provide and maintain a conducive laboratory learning environment, which is essential for students to perform laboratory safety, enhance the handling of experiments, and upgrade the safety equipment in the science laboratory.